The Development of Disaster Risk Map for Semeru Volcano Eruption 2021-2022, East Java, Indonesia - Bachri, Syamsul; Sanjaya, Eli Hendrik; Sendari, Siti; Shrestha, Rajendra Prasad; Irawan, Listyo Yudha; Billah, Egi Nursari; Putri, Nanda Regita; Prastiwi, Mellinia Regina; Hakiki, A.Riyan Rahman; Hidiyah, Tabita May (Faculty of Geography, Universitas Gadjah Mada, 2024)
The Semeru Volcano eruption on December 4, 2021 caused damage to social, economic and environmental aspects. The Rejali Watershed (DAS) is one of the areas severely affected due to the eruption. The eruption resulted in 51 deaths, 10,565 displaced people, 1,027 houses damaged, two connecting routes and 43 public facilities damaged. This study mapped the disaster risk areas due to the eruption of Semeru Volcano. This research used Laharz to analyze the lava flow hazard map and weighting for social, economic, physical, environmental, and capacity vulnerability parameters. The results showed that the risk level of Semeru Volcano eruption is divided into three classes: high, medium, and low risk. The high-risk area is 8915.09 Ha (14 %), the medium-risk area is 2174.74 Ha (17 %), and the low-risk area is 1885.60 Ha (69%). The high and medium risks were located on the upper and middle slopes of the Rejali watershed because the upstream area experiences a narrowing of the river flow (bottleneck) due to direct borders with structural land. The Semeru Volcano disaster risk map results can be used as a reference in sustainable risk management efforts in the Rejali watershed to reduce the impact and damage caused by the eruption.